Peningkatan Laju Disolusi Sistem Dispersi Padat Ibuprofen – PEG 6000 - Auzal Halim; Elvi Rahma Yulisman; Erizal Zaini (Jurnal Farmasi Higea, 2013)
It has done research on increasing the dissolution rate of solid dispersion system Ibuprofen with polymer Polyethylenglycols 6000 (PEG 6000). Solid dispersion system prepared by melting method with a ratio of raw materials Ibuprofen - PEG 6000, namely : 6:4, 7:3, 8:2, and 9:1. As a comparison was made with the physical mixture of the same composition. The powder mixture of physics and solid dispersion system properties of solids characterized by spectroscopic analysis, SEM analysis, DTA analysis, and X-ray diffraction analysis. Dissolution test method is determined by a basket. The results showed that the powder solid dispersion system can improve the physicochemical properties of Ibuprofen. Dissolution profiles showed that the 7:3 solid dispersion system powder in the 45th minute to increase the dissolution rate compared to the powder mixture of physics.